1983
DOI: 10.1080/07315724.1983.10719926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orange juice, folic acid, and oral contraceptives on serum folate in women taking a folate-restricted diet.

Abstract: The effect of folate intake from orange juice on serum folate was evaluated in 60 women (age 20-39) during 9 weeks of a folate-restricted diet. Twenty-one were users of oral contraceptives (OCA). Folate intake from the restricted diet was 159 +/- 5 micrograms/day, as assessed by dietary surveys. Serum folate of women taking OCA was lower than in nonusers at the inception of the study (P less than 0.01). During the initial 2 weeks of restricted diet, serum folates decreased significantly (13.8 +/- 1.8 to 8.5 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Orange juice was chosen since it contains mainly reduced methyl derivatives of folic acid with both free (derivatives with up to three glutamic acid residues) and conjugated (four or more glutamic acid residues) forms present. It is one of the few foods in which the folate content is sufficiently high to provide almost 200 μg in one test dose, and it has been shown to be as effective as folic acid tablets in increasing serum folate levels in OC users (Rhode et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Orange juice was chosen since it contains mainly reduced methyl derivatives of folic acid with both free (derivatives with up to three glutamic acid residues) and conjugated (four or more glutamic acid residues) forms present. It is one of the few foods in which the folate content is sufficiently high to provide almost 200 μg in one test dose, and it has been shown to be as effective as folic acid tablets in increasing serum folate levels in OC users (Rhode et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Area under the curve has also been used to compare the relative absorption of food folates with folic acid. Thus Rhode et al 175 considered that orange juice folate had over 50% bioavailability compared to folic acid when given in small daily oral doses. This contrasted with its poor bioavailability as determined by urinary excretion when given in large test doses 176…”
Section: Bioavailabilitymentioning
confidence: 99%
“…These results were confirmed in later stud ies that suggested that the low pH of the intestinal contents induced by the administration of large doses of orange juice reduced folate absorption (9). Rhode et al (32) reported that the bioavailability of folate in or ange juice was equivalent to that of oral folie acid sup plements for human subjects.…”
Section: Determination By Point Interpolation Oã-the Apparent Bioavaimentioning
confidence: 99%